A Probabilistic Cognitive Simulator For HRA Studies (PROCOS) - LEVA, CHIARA (Elsevier, 2007)
The paper deals with the development of a simulator for approaching human errors in complex operational frameworks (e.g., plant commissioning). The aim is to integrate the quanti?cation capabilities of the so-called `?rst-generation? human reliability assessment (HRA) methods with a cognitive evaluation of the operator. The simulator allows analysing both error prevention and error recovery. It integrates cognitive human error analysis with standard hazard analysis methods (Hazop and event tree) by means of a `semi static approach?. The comparison between the results obtained through the proposed approach and those of a traditional HRA method such as human error assessment and reduction technique, shows the capability of the simulator to provide coherent and accurate analysis.
PUBLISHED
Keywords: HRA; Cognitive simulation; Error recovery; Commissioning